Review paperEffect of multifactorial therapy of metabolic syndrome on the prevalence of late complications of type 2 diabetes - Poradzka, Anna; Jasik, Mariusz; Karnafel, Waldemar; Fiedor, Piotr (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2011)
The metabolic syndrome is one of the main world health problems. It causes increased cardiovascular risk and, as a result, increased mortality. It consists of enlarged waist circumference, elevated triglycerides, lowered HDL cholesterol, and elevated blood pressure and fasting glucose. It is easy to examine the majority of components in routine clinical practice, which makes diagnosis of the metabolic syndrome possible. Treatment of the metabolic syndrome components influences complications of type 2 diabetes profitably. This work briefly describes the ways of management of obesity, dyslipidaemia and hypertension, as well as antiplatelet agents and their importance in lowering the risk of occurrence of diabetic complications.